Omphalocele in Finland from 1993 to 2014: Trends, Prevalence, Mortality, and Associated Malformations-A Population-Based Study - Raitio A; Tauriainen A; Syvänen J; Kemppainen T; Löyttyniemi E; Sankilampi U; Vanamo K; Gissler M; Hyvärinen A; Helenius I (Germany, 2022)
Introduction The aim of this study is to assess the changes in prevalence, mortality and termination pregnancy of omphalocele, and to identify associated anomalies.
Materials and Methods A population-based nationwide register study. All cases with omphalocele were identified in the Finnish Register of Congenital Malformations and the Care Register for Health Care from 1993 to 2014 including live births, stillbirths, and terminations of pregnancy due to fetal anomalies. Associated anomalies were recorded and analyzed, and perinatal and infant mortality and prevalence were calculated.
Results There were 600 cases with omphalocele including 229 live births, 39 stillbirths, and 332 (55%) abortions. Birth prevalence in Finland was 1.96 per 10,000 births with no consistent trend over time. However, total prevalence was much higher (4.71/10,000) because more than half of these families chose option for the termination of pregnancy. Omphalocele is often complicated with other anomalies; most commonly chromosomal abnormalities (9.3%), heart defects (6.3%), central nervous system anomalies (3.0%), gastrointestinal, and urogenital malformations (both 2.0%). Proportion of chromosomal and central nervous system abnormalities were even higher in terminated pregnancies. Overall infant mortality was 22%. Total 1-year survival rates for isolated omphalocele, cases with multiple anomalies and neonates with chromosomal defects were 80, 88, and 17%, respectively.
Conclusion Omphalocele is a rare congenital anomaly, often associated with other malformations. Our data suggest that isolated cases may be more common than previously thought. In the absence of chromosomal defects, survival is reasonably good. Regardless, more than half of these pregnancies are often terminated.